Hydrophobic deep eutectic solvents as novel, sustainable aids for intracellular protein release from Saccharomyces cerevisiae - Tjalling Gijsbert Tjalsma; Yannick Patrice Didion; Ziran Su; Magdalena Malankowska; Pablo Torres-Montero; José Luis Martínez; Manuel Pinelo (Results in Engineering)
Saccharomyces cerevisiae (S. cerevisiae) is a microorganism of high interest due to its applications in pharmaceutical and food industries. However, traditional downstream processing of intracellular compounds often depends on organic solvents and harsh processing conditions. Here, the use of hydrophobic deep eutectic solvents (DESs) as cell wall permeabilization agents for intracellular protein release from Saccharomyces cerevisiae was studied for the first time. This study examines the relatively new type V DESs, which favors downstream methods because less solvent is needed and environmentally friendly substances can be used. The DESs were synthesized from L-menthol, lidocaine, acetic acid, decanoic acid, oleic acid and lauric acid, and screened for viability. Next, 0.5 wt% DES was mixed in a mild alkaline buffer containing S. cerevisiae. Despite the similar structures of the hydrogen bond acceptor (HBA) and hydrogen bond donor (HBD), DESs with L-menthol and lidocaine as HBA and a fatty acid as HBD exhibited superior performance compared to DESs consisting solely of L-menthol and lidocaine or those derived from fatty acids only. DES lidocaine:decanoic acid 1:3 resulted in a protein yield of 2.45 (±0.03) mg/mL, which outperformed a method using a standard lysis reagent that resulted in 2.33 (±0.04) mg/mL. It was concluded that the underlying linkages between HBA and HBD play a key role because different HBA and HBD combinations have a bearing on whether protein release is successful.